Representações de alunos sobre ensinar-aprender inglês e seu (des)interesse em estudar essa língua - Souza, Zico Ferreira de (2009)
This research aims to investigate the students representations of the English Language teaching-learning process in Elementary School (Ensino Fundamental) at a São Paulo State Government School. It also examines the relationship between those representations and the reasons why students are leaded to disinterest or lose of interest in studying English in this context. This research is grounded on the Behaviorist, Cognitivist, Humanist and Socio-intereactionist teaching-learning theories as well as on the Brazilian National Curriculum Parameters (Parâmetros Curriculares Nacionais LE, 1998) and the view of language as social practice (Bakhtin, 1977/2006). This research is also based on the social representation theory of Jodelet (2001) and Moscovic (2003). This study took place in a state government school located in a suburb of Diadema, a city in Greater São Paulo, where 16 students were investigated (4 students from each grade). The data were collected through interviews and questionnaires in October and November, 2007. The results show that the students were not disinterested nor did they lose their interest in studying English. In some cases, the interest decreased because the students felt they could not learn the language. This way, we may conclude that getting to know the representations and the factors that lead to students interest decrease in their English classes may suggest that teaching- learning strategies should take into account the relevance of what to teach and how to teach so as to keep and increase the students interest in learning English